Guardrails guiding human decisions in the age of AI - Gasser, Urs 1972-; Mayer-Schönberger, Viktor 1966- (Princeton University Press, 2024)
"In making decisions-be they decisions for ourselves, our families, our work, or our government-our thinking is informed by a host of factors that include the information we have on hand, the societal norms exerting pressure in one direction or another, the laws that govern us, and, increasingly, the technology that can bring the power of algorithms, AI, and computing to our aid. Viktor Mayer-Schönberger and Urs Gasser term this overarching set of external influences "guardrails": the structures, much like the same-named barriers on highways, that establish the bounds and direction of desirable behavior. As technology has come to play an outsized role in shaping our decision-making, the authors argue that a clear understanding of what role guardrails can and should play in our society is essential-and that this in turn can help us determine what kind of transparency and accountability we require of the technology we rely on. The authors first consider some of the challenges of decision-making in the digital world in chapters that focus on information and misinformation, human bias and the promise (or not) of AI to correct it, and decision-making in the face of uncertainty. In each case, they show how the quick embrace of technological solutions can lead to results we don't expect or hope for (for instance, the perpetuation of racial discrimination in the algorithmic assessment of credit-worthiness). They then lay out what they see as the key principles for good guardrails-empowering individual decisions, accounting for the social good, and flexibility in the face of new circumstances. Ultimately, the authors present a vision for the future of decision-making that centers individual choice and human volition even in face of technological progress."
Keywords: Decision making; Computers and civilization; Technological innovations; Künstliche Intelligenz; Entscheidungstheorie